Mott schottky heterojunction nanomaterials, methods of making and uses thereof

CN116180139BActive Publication Date: 2026-10-16XIANGTAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310187669.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-02
Publication Date
2026-10-16
Estimated Expiration
2043-03-02

AI Technical Summary

Technical Problem

研究表明Ru、Ir、Pt等贵金属及其氧化物具有最优异的析氢催化性能,但其价格昂贵、资源匮乏限制了这些材料的广泛应用

Benefits of technology

[0027] The NiFe2O4/Ni2P Mott-Schottky heterojunction nanomaterials of this application possess a stable structure and electron interactions conducive to catalysis, exhibiting excellent total hydrolysis activity with a total hydrolysis current density of 10 mA cm⁻¹. -2 At that time, the required voltage is only 1.48V, and the current density is 10mA cm⁻¹. -2 It can operate continuously for 50 hours without significant degradation, thus exhibiting excellent stability. Furthermore, the material does not contain rare or precious metal elements, resulting in low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116180139B_ABST
    Figure CN116180139B_ABST
Patent Text Reader

Abstract

The application relates to a NiFe2O4 / Ni2P Mott-Schottky heterojunction nanomaterial, which has a stable structure and an electronic interaction beneficial to catalysis, has excellent full-hydrolysis activity, and has an excellent stability. ‑2 When the full-hydrolysis current density is 10 mA cm ‑2 , the required voltage is only 1.48 V, and the material can continuously work for 50 hours without obvious attenuation when the current density is 10 mA cm ‑2 , and therefore has the advantage of good stability. Meanwhile, the material does not contain rare or noble metal elements, and is low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of electrochemical catalysis technology, and in particular relates to a NiFe2O4 / Ni2P Mott-Schottky heterojunction nanomaterial, its preparation method, and its applications. Background Technology

[0002] In recent years, the oxygen evolution reaction (OER) has been widely used in sustainable energy conversion systems such as water splitting devices and metal-air batteries, highlighting its increasing importance in the field of basic catalysis. The preparation of inexpensive and efficient OER catalysts has been a hot topic in scientific research at universities and in enterprises. OER catalysts include transition metal-based oxides, hydroxides, sulfides, and phosphides. Meanwhile, to further improve electrocatalytic performance, researchers have developed techniques such as morphology control, heteroatom doping, defect introduction, and heterostructure engineering.

[0003] Generally speaking, heterostructures with strong interfacial interactions can trigger electron redistribution within the heterostructure interface, thereby regulating the electronic structure, optimizing the adsorption energy of intermediates, and even endowing them with synergistic effects, providing an effective strategy for enhancing the intrinsic activity of active sites.

[0004] Many reported Schottky heterojunction catalysts have made significant contributions to OER performance. For example, the NiFeLDH / NiS Schottky heterojunction exhibits remarkable OER activity. In this catalytic system, the abundant porosity of the NiS nanosheet array contributes to abundant catalytic sites and good electrolyte permeability, thereby achieving rapid mass transfer. Furthermore, theoretical calculations show that the coupling of NiFe LDH and NiS can adjust the binding strength between the d-band center of Ni(Fe) atoms and the oxygen intermediate, thus obtaining good OER kinetics (QLWen, K. Yang, DJ Huang, YWLiu and HQLi, Adv. Energy Mater., 2021, 11, 2102353.). However, to our knowledge, few have combined NiFe2O4 with Ni2P for OER and water electrolysis applications. The key to the large-scale application of water electrolysis is how to reduce the OER overpotential, achieve high-current hydrogen production at low potentials, and thus reduce energy consumption and hydrogen production costs. Studies have shown that noble metals such as Ru, Ir, and Pt, and their oxides, possess superior hydrogen evolution catalytic performance; however, their high cost and scarcity limit their widespread application. Therefore, a low-cost, high-efficiency non-noble metal catalyst for water electrolysis is needed. Summary of the Invention

[0005] The technical problem to be solved by this invention is to overcome the shortcomings of the prior art and provide a low-cost and high-efficiency NiFe2O4 / Ni2P Mott-Schottky heterojunction nanomaterial, its preparation method and uses.

[0006] The technical solution adopted by this invention to solve its technical problem is:

[0007] A method for preparing NiFe2O4 / Ni2P heterojunction nanomaterials includes the following steps:

[0008] S1: Dissolve Fe(NO3)3 and Ni(NO3)2 or a hydrate of the two substances in ethylene glycol and stir until homogeneous. Then add sodium dodecyl sulfonate and stir until homogeneous. Transfer the mixture to a hydrothermal reactor for hydrothermal reaction. Take the precipitate, wash it, and dry it to obtain the oxide precursor.

[0009] S2: Calcine the oxide precursor prepared in step S1 to obtain brown NiFe2O4;

[0010] S3: Dissolve Ni(NO3)2 and hexamethylenetetramine in deionized water to obtain a clear solution; then grind the NiFe2O4 obtained in step S2 and add it to the clear solution, stir evenly, and carry out a hydrothermal reaction. After the hydrothermal reaction, take the precipitate, wash and dry the product to obtain NiFe2O4 / Ni(OH)2.

[0011] S4: Sodium hypophosphite or its hydrate and the NiFe2O4 / Ni(OH)2 powder obtained in step S3 are placed in a ceramic boat and placed in the upstream and downstream of a tube furnace respectively. They are heated in an oxygen-free atmosphere to obtain the final product: NiFe2O4 / Ni2P.

[0012] in:

[0013] The SDS added in step S1 is a surfactant that can increase the specific surface area of ​​the product. It will evaporate at high temperature during the subsequent calcination in step S2, and will not affect the purity of the final product.

[0014] The NiFe₂O₄ obtained in step S2 is a p-type semiconductor with a unique spinel structure, in which Ni is a +2 valence ion and Fe is a +3 valence ion. 2+ Occupying tetrahedral sites, Fe 3+ Occupying octahedral sites. This spinel transition metal oxide has been shown to be a promising catalyst, exhibiting good chemical stability, high corrosion resistance, abundant natural resources, multiple oxidation states, and is inexpensive and environmentally friendly, making it applicable in many fields.

[0015] In step S3, HMTA is crucial for ensuring the solution is alkaline, as hydroxide formation requires an alkaline environment.

[0016] The final product obtained in step S4 is a Motter-Schottky heterojunction catalyst combining p-type NiFe₂O₄ and Ni₂P. This catalyst overcomes two drawbacks: the electrochemical instability caused by the small specific surface area and easy aggregation of NiFe₂O₄, and the lack of sufficient surface active sites in Ni₂P, which hinders its practical application. Based on the Schottky heterostructure, a built-in electric field exists between NiFe₂O₄ and Ni₂P, inducing self-driven charge transfer at the interface, promoting the absorption of reactant molecules and the breaking of chemical bonds, thereby triggering water splitting.

[0017] Preferably, in the preparation method of NiFe2O4 / Ni2P heterojunction nanomaterials of the present invention, the hydrothermal reaction temperature in step S1 is 160℃~170℃, and the reaction time is 10~15h.

[0018] Preferably, in the preparation method of the NiFe2O4 / Ni2P heterojunction nanomaterial of the present invention, the calcination in step S2 is carried out in a muffle furnace at 2-3°C for 1 minute. -1 Calcination was carried out at a heating rate of 450–460℃ for 2–3 hours.

[0019] Preferably, in the preparation method of NiFe2O4 / Ni2P heterojunction nanomaterials of the present invention, the hydrothermal reaction temperature in step S3 is 95-105°C and the reaction time is 8-10 hours.

[0020] Preferably, in the preparation method of NiFe2O4 / Ni2P heterojunction nanomaterials of the present invention, the mass ratio of sodium hypophosphite hydrate to NiFe2O4 / Ni(OH)2 powder in step S4 is 5:1.

[0021] Preferably, in the preparation method of the NiFe2O4 / Ni2P heterojunction nanomaterial of the present invention, step S4 involves heating at 350–360°C for 2 hours, with a heating rate of 2–3°C / min. -1 .

[0022] Preferably, in the preparation method of NiFe2O4 / Ni2P heterojunction nanomaterials of the present invention, the oxygen-free atmosphere in step S4 is a nitrogen atmosphere.

[0023] The present invention also provides a NiFe2O4 / Ni2P heterojunction nanomaterial, which is prepared by the above-described preparation method.

[0024] The present invention also provides a carbon fiber cloth anode material, the surface of which is coated with the above-mentioned NiFe2O4 / Ni2P material.

[0025] The present invention also provides the application of the carbon fiber cloth anode material as described above as an anode in water electrolysis.

[0026] The beneficial effects of this invention are:

[0027] The NiFe2O4 / Ni2P Mott-Schottky heterojunction nanomaterials of this application possess a stable structure and electron interactions conducive to catalysis, exhibiting excellent total hydrolysis activity with a total hydrolysis current density of 10 mA cm⁻¹. -2 At that time, the required voltage is only 1.48V, and the current density is 10mA cm⁻¹. -2 It can operate continuously for 50 hours without significant degradation, thus exhibiting excellent stability. Furthermore, the material does not contain rare or precious metal elements, resulting in low cost. Attached Figure Description

[0028] The technical solution of this application will be further described below with reference to the accompanying drawings and embodiments.

[0029] Figure 1 This is a synthesis route diagram of the NiFe2O4 / Ni2P Schottky heterojunction nanomaterials in this application;

[0030] Figure 2 This is a microstructure diagram of the NiFe2O4 / Ni2P Schottky heterojunction nanomaterial in this application;

[0031] Figure 3 These are the structural and morphological characterization images of the NiFe2O4 / Ni2P Schottky heterojunction nanomaterials in this application, where (a) is an XRD pattern; (b) is a TEM image; (c) is a high-resolution transmission electron microscope (HR-TEM) image; and (d) is the corresponding selected area electron microscope (SAED) image.

[0032] Figure 4 These are the OER test results of the NiFe2O4 / Ni2P Schottky heterojunction nanomaterials in this application, including (a) LSV plot; (b) Tafel plot; (c) EIS plot; (d) CDL curve; (e) CV plot of NiFe2O4 / Ni2P at different scan rates; (f) Ea comparison plot; and (g) OER plot of NiFe2O4 / Ni2P at 10 mA cm⁻¹. -2 The following is a 24-hour stability graph; (h) is a performance comparison graph of NiFe2O4 / Ni2P with other reported catalysts.

[0033] Figure 5 The graph shows the test results of a battery assembled with NiFe2O4 / Ni2P catalysts and subjected to full hydrolysis. (a) shows the comparative polarization curves of batteries assembled with NiFe2O4 / Ni2P||Pt / C and those assembled with single-phase catalysts; (b) shows the polarization curves of NiFe2O4 / Ni2P||Pt / C at 10 mA cm⁻¹. -2 Stability testing will then be conducted.

[0034] Figure 6The graph shows the test results obtained by full electrolysis of NiFe2O4 / Ni2P catalyst in simulated brine, where (a) is the LSV curve of the catalyst in 0.5M NaCl + 1M KOH solution; and (b) is the LSV curve of the catalyst in two electrolyte solutions at 10 mA cm⁻¹. -2 and 50mA cm -2 (c) Comparison of overpotentials under two electrolytes; (d) Comparison of polarization curves of NiFe2O4 / Ni2P||Pt / C battery under two electrolytes; (e) 24-hour stability test of NiFe2O4 / Ni2P||Pt / C battery in 0.5M NaCl+1M KOH solution. Detailed Implementation

[0035] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other.

[0036] Example 1

[0037] This embodiment provides a method for preparing NiFe2O4 / Ni2P heterojunction nanomaterials, including:

[0038] S1: Dissolve 0.303g Fe(NO3)3·9H2O and 0.1120g Ni(NO3)2·6H2O in 30mL ethylene glycol (EG) and stir for 30 minutes. Then add 0.32g sodium dodecyl sulfonate (SDS) and stir vigorously with a magnetic stirrer for two to three hours. Transfer the mixture to a 50mL hydrothermal reactor and react at 160℃ for 15 hours. After natural cooling, wash the precipitate three times each with deionized water and alcohol, centrifuge, and then dry it in a vacuum drying oven at 60℃ for 8 hours to obtain the oxide precursor.

[0039] S2: Place the oxide precursor prepared in step S1 into a muffle furnace and heat at 2℃ for min. -1 Calcination at 450℃ for 2 hours at a heating rate of [unspecified] yielded brown NiFe2O4 (which served as both a precursor and a control sample for subsequent testing).

[0040] S3: Dissolve 0.21g Ni(NO3)2 and 0.62g hexamethylenetetramine (HMTA) completely in 36mL deionized water and stir for 30 minutes to obtain a clear solution; then grind the NiFe2O4 obtained in step S2 and add it to the above solution, stir vigorously for 30 minutes, then transfer it to a 50mL hydrothermal reactor and hydrothermally heat at 95℃ for 8 hours. The product after washing and drying is NiFe2O4 / Ni(OH)2.

[0041] S4: 250 mg of sodium hypophosphite monohydrate and 50 mg of NiFe2O4 / Ni(OH)2 powder obtained in step S3 were placed in porcelain boats and placed in the upstream and downstream sections of a tube furnace, respectively. The furnace was heated at 350 °C for 2 hours under a N2 atmosphere, with a heating rate of 2 °C / min. -1 The final product obtained is NiFe2O4 / Ni2P.

[0042] Example 2

[0043] This embodiment provides a method for preparing NiFe2O4 / Ni2P heterojunction nanomaterials, including:

[0044] S1: Dissolve 0.306 g Fe(NO3)3·9H2O and 0.1118 g Ni(NO3)2·6H2O in 30 mL ethylene glycol (EG) and stir for 30 minutes. Then add 0.33 g sodium dodecyl sulfonate (SDS) and stir vigorously with a magnetic stirrer for two to three hours. Transfer the mixture to a 50 mL hydrothermal reactor and react at 165 °C for 12 hours. After natural cooling, wash the precipitate three times each with deionized water and alcohol, centrifuge, and then dry it in a vacuum drying oven at 70 °C for 8 hours to obtain the oxide precursor.

[0045] S2: Place the oxide precursor obtained in step S1 into a muffle furnace and heat at 2℃ for min. -1 Calcination at 455℃ for 2 hours at a heating rate of [unspecified] yielded brown NiFe2O4 (which served as both a precursor and a control sample for subsequent testing).

[0046] S3: Dissolve 0.22g Ni(NO3)2 and 0.61g hexamethylenetetramine (HMTA) completely in 38mL deionized water and stir for 32 minutes to obtain a clear solution; then grind the NiFe2O4 obtained in step S2 and add it to the above solution, stir vigorously for 32 minutes, then transfer it to a 50mL hydrothermal reactor and hydrothermally heat at 100℃ for 8 hours. The product after washing and drying is NiFe2O4 / Ni(OH)2.

[0047] S4: 252 mg of sodium hypophosphite monohydrate and 52 mg of NiFe2O4 / Ni(OH)2 powder obtained in step S3 were placed in porcelain boats and placed in the upstream and downstream sections of a tube furnace, respectively. The furnace was heated at 35 °C for 2 hours under a N2 atmosphere, with a heating rate of 2.5 °C / min. -1 The final product obtained is NiFe2O4 / Ni2P.

[0048] Example 3

[0049] This embodiment provides a method for preparing NiFe2O4 / Ni2P heterojunction nanomaterials, including:

[0050] S1: Dissolve 0.310 g Fe(NO3)3·9H2O and 0.1116 g Ni(NO3)2·6H2O in 30 mL ethylene glycol (EG) and stir for 30 minutes. Then add 0.34 g sodium dodecyl sulfonate (SDS) and stir vigorously with a magnetic stirrer for two to three hours. Transfer the mixture to a 50 mL hydrothermal reactor and react at 170 °C for 10 hours. After natural cooling, wash the precipitate three times each with deionized water and alcohol, centrifuge, and then dry it in a vacuum drying oven at 80 °C for 8 hours to obtain the oxide precursor.

[0051] S2: Place the oxide precursor prepared in step S1 into a muffle furnace and heat at 2℃ for min. -1 Calcination at 460℃ for 2 hours at a heating rate of [unspecified rate] yielded brown NiFe2O4;

[0052] S3: Dissolve 0.23g Ni(NO3)2 and 0.6g hexamethylenetetramine (HMTA) completely in 40mL deionized water and stir for 35 minutes to obtain a clear solution; then grind the NiFe2O4 obtained in step S2 and add it to the above solution, stir vigorously for 35 minutes, then transfer it to a 50mL hydrothermal reactor and hydrothermally heat at 105℃ for 8 hours. The product after washing and drying is NiFe2O4 / Ni(OH)2.

[0053] S4: 255 mg of sodium hypophosphite monohydrate and ~55 mg of NiFe2O4 / Ni(OH)2 powder obtained in step S3 were placed in porcelain boats and placed in the upstream and downstream sections of a tube furnace, respectively. The furnace was heated at 360 °C for 2 hours under a N2 atmosphere, with a heating rate of 3 °C / min. -1 The final product obtained is NiFe2O4 / Ni2P.

[0054] The morphology of the NiFe2O4 / Ni2P heterostructure nanomaterials prepared in Example 1 was observed and tested, and the following results were obtained: Figure 2 and Figure 3 . Figure 3Figure (a) shows the XRD pattern of the nanomaterial; (b) shows the TEM image; (c) shows the high-resolution transmission electron microscope (HR-TEM) image; and (d) shows the corresponding selected area electron microscope (SAED) image. From (a), it can be seen that NiFe₂O₄ / Ni₂P and the control samples NiFe₂O₄ and Ni₂P all correspond to the standard card, indicating that the three substances were successfully synthesized. Specifically, NiFe₂O₄ (JCPDS: 10-0325) is matched at positions of 30.3°, 35.7°, 37.3°, 43.5°, and 53.5°, while Ni₂P (JCPDS: 03-0953) is matched at positions of 40.8°, 44.6°, 47.3°, and 54.2°. The figure shows that NiFe₂O₄ / Ni₂P consists of these two phases, without any other impurities. (b) is a TEM image of the NiFe2O4 / Ni2P catalyst. As can be seen from the image, NiFe2O4 / Ni2P maintains a nanoparticle morphology. From the HRTEM images in (c) and (d), it can be seen that the lattice spacings of 0.203 nm and 0.208 nm correspond to the (201) and (400) crystal planes of Ni2P and NiFe2O4, respectively, and there is a clear interface between the two types of stripes, indicating that the NiFe2O4 / Ni2P heterojunction catalyst was successfully synthesized.

[0055] Comparative Examples

[0056] The brown NiFe2O4 and Ni2P materials obtained in step S2 of Example 1 were used as comparative materials for OER performance testing and water electrolysis hydrogen production performance testing.

[0057] The preparation process of Ni2P material is as follows:

[0058] S1: Dissolve 0.21g Ni(NO3)2 and 0.62g hexamethylenetetramine (HMTA) completely in 36mL of deionized water and stir for 30 minutes to obtain a clear solution; transfer the clear solution into a 50mL hydrothermal reactor and hydrothermally heat at 95℃ for 8 hours; the product after washing and drying is Ni(OH)2.

[0059] S2: 250 mg of sodium hypophosphite monohydrate and 50 mg of Ni(OH)₂ powder obtained in step S1 were placed in porcelain boats and placed upstream and downstream of a tube furnace, respectively. The mixture was heated at 350 °C for 2 hours under a N₂ atmosphere, with a heating rate of 2 °C / min. -1 Ni2P is obtained.

[0060] Effect Example

[0061] OER performance test:

[0062] The OER performance of the NiFe2O4 / Ni2P nanomaterials from Example 1 was tested, and the results are as follows: Figure 4As shown, it exhibits excellent OER performance with a current density of 10 mA cm⁻¹. -2 The overpotential is only 260mV, and the Tafel slope is 60mV dec. -1 It outperforms many heterojunction catalysts; at 10 mA cm⁻¹ -2 Stability tests were conducted at low current densities for 24 hours, showing minimal performance degradation. Even at high current densities, the performance remained respectable. When assembled into a battery for complete hydrolysis, the NiFe2O4 / Ni2P||Pt / C battery achieved 10 mA cm⁻¹ at only 1.48V. -2 The catalyst exhibits a stable current density and maintains this stability for 50 hours. Furthermore, it was tested in a simulated brine electrolyte using both a three-electrode and a two-electrode configuration, demonstrating continued stability and further proving the strong corrosion resistance of the NiFe2O4 / Ni2P catalyst.

[0063] Electrolysis of water to produce hydrogen performance test:

[0064] The NiFe2O4 / Ni2P catalyst from Example 1 was assembled into a battery for complete water splitting. The anode and cathode were coated with catalyst ink and commercial Pt / C ink (prepared using the same method as the NiFe2O4 / Ni2P catalyst ink, except that the catalyst was replaced with Pt / C), respectively. The carbon cloth (working area: 1×1cm) was coated with catalyst ink and commercial Pt / C ink (prepared using the same method as the NiFe2O4 / Ni2P catalyst ink, except that the catalyst was replaced with Pt / C). 2 The loading capacity is 2.5 mg cm. -2 The electrolyte was a 1M KOH solution. Two pieces of carbon cloth were clamped together with working electrode clamps, and water electrolysis to produce hydrogen was performed at a working voltage of 1.0V–2.0V vs. RHE. The test results are as follows: Figure 5 As shown.

[0065] Due to its stable structure and the electronic interactions between catalysts, NiFe2O4 / Ni2P nanocatalysts exhibit excellent total hydrolysis activity, with a total hydrolysis current density of 10 mA cm⁻¹. -2 At that time, the required voltage is only 1.48V, and the current density is 10mA cm⁻¹. -2 It can work continuously for 50 hours without significant degradation, proving that its stability is very good.

[0066] The NiFe2O4 / Ni2P catalyst was tested by electrolyzing brine in simulated brine. The test results are as follows: Figure 6 As shown, due to Cl -The presence of certain substances makes electrocatalytic stability in brine a challenging task, potentially compromising the long-term stability of the battery. Therefore, stability in brine media is another crucial characteristic of catalysts. NiFe₂O₄ / Ni₂P, due to its stable structure and interactions, exhibits good corrosion resistance and high stability in brine. Compared to alkaline solutions, the performance of this catalyst tested in brine showed no significant degradation.

[0067] In the embodiments of this application, the NiFe2O4 / Ni2P catalyst refers to the NiFe2O4 / Ni2P nanomaterial.

[0068] Based on the above-described preferred embodiments according to this application, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the technical concept of this application. The technical scope of this application is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A method for preparing NiFe2O4 / Ni2P heterojunction nanomaterials, characterized in that, Includes the following steps: S1: Dissolve Fe(NO3)3 and Ni(NO3)2 or a hydrate of the two substances in ethylene glycol and stir until homogeneous. Then add sodium dodecyl sulfonate and stir until homogeneous. Transfer the mixture to a hydrothermal reactor for hydrothermal reaction. Take the precipitate, wash it, and dry it to obtain the oxide precursor. S2: Calcine the oxide precursor prepared in step S1 to obtain brown NiFe2O4; S3: Dissolve Ni(NO3)2 and hexamethylenetetramine in deionized water to obtain a clear solution; then grind the NiFe2O4 obtained in step S2 and add it to the clear solution, stir evenly, and carry out a hydrothermal reaction. After the hydrothermal reaction, take the precipitate, wash and dry the product to obtain NiFe2O4 / Ni(OH)2. S4: Sodium hypophosphite or its hydrate and the NiFe2O4 / Ni(OH)2 powder obtained in step S3 are placed in a ceramic boat and placed in the upstream and downstream of a tube furnace respectively. They are heated in an oxygen-free atmosphere to obtain the final product: NiFe2O4 / Ni2P. The hydrothermal reaction temperature in step S1 is 160℃~170℃, and the reaction time is 10~15 hours; In step S2, calcination is carried out in a muffle furnace at 2–3 °C for 1 minute. -1 Calcination at 450–460℃ for 2–3 hours at a heating rate of [missing information]; In step S3, the hydrothermal reaction temperature is 95℃~105℃, and the reaction time is 8~10 hours; In step S4, heating is carried out at 350–360°C for 2 hours, with a heating rate of 2–3°C / min. -1 .

2. The method for preparing NiFe2O4 / Ni2P heterojunction nanomaterials according to claim 1, characterized in that, In step S4, the mass ratio of sodium hypophosphite hydrate to NiFe2O4 / Ni(OH)2 powder is 5:

1.

3. The method for preparing NiFe2O4 / Ni2P heterojunction nanomaterials according to claim 1, characterized in that, The oxygen-free atmosphere in step S4 is a nitrogen atmosphere.

4. A NiFe2O4 / Ni2P heterojunction nanomaterial, characterized in that, It is prepared by the preparation method according to any one of claims 1-3.

5. A carbon fiber cloth anode material, the surface of which is coated with the NiFe2O4 / Ni2P material as described in claim 4.

6. The application of the carbon fiber cloth anode material as described in claim 5 as an anode in water electrolysis.